Anti-Crisis Management in Tourism Enterprises: Theoretical and Methodological Foundations and Practical Recommendations (Economics and region, 2024)
The article explores the theoretical and methodological foundations of crisis management in tourism enterprises, aiming to offer practical recommendations for effectively implementing crisis measures. The research focuses on identifying modern approaches to crisis management within the tourism industry, particularly in light of the dynamic challenges posed by external crises. It examines the key factors influencing the resilience of tourism enterprises during times of crisis, such as economic fluctuations, geopolitical tensions, and shifting consumer behaviour. The article highlights the importance of strategic planning, crisis response mechanisms, and the integration of innovative technologies, such as digital platforms, in managing crises. Practical recommendations for tourism agencies and operators are provided to help them navigate crisis conditions, optimize costs, diversify services, and adapt to changing market demands. Ultimately, the research emphasizes the need for a holistic crisis management strategy that ensures the sustainability and recovery of tourism enterprises in uncertain environments.
Keywords: anti-crisis management; tourism business; strategic planning; crisis management; innovations in tourism; service diversification